Colchicine lack of effectiveness in symptom and inflammation modification in knee osteoarthritis (COLKOA): a randomized controlled trial. Issue 5 (May 2018) - Leung, Y.Y.; Haaland, B.; Huebner, J.L.; Wong, S.B.S.; Tjai, M.; Wang, C.; Chowbay, B.; Thumboo, J.; Chakraborty, B.; Tan, M.H.; Kraus, V.B.
Summary: Objectives: Uric acid may activate an innate immune response in osteoarthritis (OA), contributing to disease pathology and progression. We evaluated the effectiveness of colchicine on pain and function in symptomatic knee OA (KOA) and the underlying mechanism of action. Methods: Colchicine effectiveness in symptoms and inflammation modification in knee osteoarthritis (COLKOA) was a double-blind, placebo-controlled, randomized trial comparing 16 weeks of treatment with 0.5 mg twice-daily oral colchicine to placebo for knee osteoarthritis (KOA). The primary endpoint was ≥30% improvement in total Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score at week 16. Secondary endpoints included improvement in pain (0–10 Likert scales); WOMAC pain; patient global assessment (0–100); physical function; the OARSI-OMERACT response; quality of life; and change in serum, urine, synovial fluid (SF) biomarkers of cartilage metabolism and inflammation, and plasma/SF colchicine concentrations. Results: Of 109 randomly assigned participants, 39% (95% confidence interval (CI) 27–52%) and 49% (95% CI 36–62%) in the colchicine and placebo arms respectively met the primary endpoint at study end ( P = 0.284, odds ratio 0.66, 95% CI 0.31–1.41). No strong evidence of treatment differences was identified on clinical secondary endpoints. Treatment significantly reduced mean serum hs-CRP ( P = 0.008) and SF CTXI ( P = 0.002); treatment tended to reduce inflammatory markers (SF IL-6, IL8, TNFα, CD14 and IL-18), but these differences were not statistically significant. Conclusion: Colchicine (0.5 mg twice-daily orally) reduced inflammation and high bone turnover biomarkers known to be associated with OA severity and progression risk, but did not reduce KOA symptoms over a 16-week study period. A longer-term study to evaluate for slow-acting disease modifying effects is warranted. Trial registration: The trial has been registered at clinicaltrials.gov asNCT02176460 . Date of registration: June 26, 2014.